Dynamique des réponses aérobies lors d`un 100 m nage libre, réalisé dans des conditions de compétition - Jalab, C.; Enea, C.; Delpech, N.; Bernard, O. (Applied Physiology, Nutrition, and Metabolism, 2010)
The main purpose of this study is to estimate the dynamics of oxygen uptake (VO2) during a 100 m front crawl event, performed in competition conditions. Eleven trained swimmers participated in 2 separate sessions, in a 25 m swimming pool. Maximal oxygen uptake (VO2max) was determined during a 400 m maximal event. Swimmers also performed a 100 m front crawl in competition conditions, and then, 3 tests (25, 50, and 75 m) following the pacing strategy of the 100 m event. To be free of technical constraints, VO2 was not measured during the tests, but before and just at the end of each test with a 1 min breath-by-breath method. Each post-test VO2 measurement (after 25, 50, 75, and 100 m) allows us to reconstruct the VO2 kinetics of the 100 m performance. Our results differ from previous studies in that VO2 increases faster in the first half of the race (at 50 m, VO2 ˜ 94% VO2max), reaches VO2max at the 75 m mark; then a decrease in VO2 corresponding to 7% of VO2max appears during the last 25 m. These differences are supposed to be mainly the consequences of the adoption of technical elements and a pacing strategy similar to competition conditions. In the future, these observations may lead to different considerations of the bioenergetic contributions.